GUERRILLA MARKETING: DILEMA EFISIENSI BIAYA DANEFEKTIFITAS PROMOSI DALAM MENDAPATKAN KONSUMEN - Mulyanto, Kukuh (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2014)
Nowadays people’s knowledge is getting bigger, so itmakesthe marketers have to develop their promotiontechnique becomes better for getting the increase numberof the consumers. At first, guerrilla marketing is used bysmall business because it need not a big fund but it is ableto produce a lot of products. In real life, to do a guerrillamarketing strategy needs higher cost. Otherwise, thereare a lot of big companies which is used guerrillamarketing strategy. When doing guerrilla, especially thesmall enterprises they have to think about the resource sothat the enterprise can get the value of consumer that theywant matched with the cost.